2022
DOI: 10.3390/diagnostics12102414
|View full text |Cite
|
Sign up to set email alerts
|

Serum Lactate as Serum Biomarker for Cardiopulmonary Parameters within the First 24 Hours after a Spontaneous Intracerebral Hemorrhage

Abstract: Objective: Cardiopulmonary (CP) complications are well known in patients with an intracerebral hemorrhage (ICH) and could be associated with a higher serum lactate level. The present study aimed to assess the associations between the initial serum lactate level and the CP parameters within the first 24 h of intensive care unit (ICU) treatment in neurosurgical ICH patients. Patients and Methods: A total of 354 patients admitted to the ICU between 01/2009 and 12/2017 with a diagnosis of an ICH were retrospective… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 35 publications
0
3
0
Order By: Relevance
“…Therefore, when assessing the disease severity and predicting clinical outcomes in patients with CRC requiring ICU admission, it might be more useful to consider serum LA levels instead of serum LDH. Previous studies have highlighted that serum LA levels are commonly used as a biomarker in ICUs to assess disease severity and predict outcomes in various conditions, including sepsis, septic shock, cardiac arrest, trauma, local ischemia, and liver dysfunction [ 40 ]. One possible explanation is that, in the case of patients with CRC admitted to the ICU, the detrimental effects of severe complications and impaired circulatory organ function may outweigh the impact of the tumor itself.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, when assessing the disease severity and predicting clinical outcomes in patients with CRC requiring ICU admission, it might be more useful to consider serum LA levels instead of serum LDH. Previous studies have highlighted that serum LA levels are commonly used as a biomarker in ICUs to assess disease severity and predict outcomes in various conditions, including sepsis, septic shock, cardiac arrest, trauma, local ischemia, and liver dysfunction [ 40 ]. One possible explanation is that, in the case of patients with CRC admitted to the ICU, the detrimental effects of severe complications and impaired circulatory organ function may outweigh the impact of the tumor itself.…”
Section: Discussionmentioning
confidence: 99%
“…First, ICH usually triggers a stress response in the body, which can lead to a disorder in the internal environment. Patients with ICH experience microcirculatory dysfunction and hypermetabolic conditions that lead to lactate accumulation in the brain (39)(40)(41)(42). ICH induces an acute inflammatory response due to reduced hepatic synthesis of albumin and increases the endothelial permeability of albumin from the vasculature into the extravascular space, decreasing serum albumin concentration (43)(44)(45).…”
Section: Discussionmentioning
confidence: 99%
“…Currently, a larger volume and expansion of ICH, lower level of consciousness, lower Glasgow Coma Scale (GCS) score, advanced age, larger peri-hemorrhagic edema, and the presence of an intraventricular hemorrhage (IVH) and hydrocephalus are the most frequently used early predictors for mortality and poor outcome in ICH patients [8][9][10][11][12][13]. In addition to these well-known predictors, several studies have demonstrated the benefit of serum biomarkers, e.g., elevated levels of C-reactive protein (CRP), troponin I, cortisol, blood glucose, serum lactate, and white blood cell count, as well as CRP-to-albumin and fibrinogen-to-albumin ratios, to predict poor outcome and increased mortality in ICH patients [6,[14][15][16][17][18][19][20].…”
Section: Introductionmentioning
confidence: 99%